Assessing Brevibacillus sp. C17: An indigenous isolated bacterium as bioremediator for agrochemical effluent containing toxic carbendazim. (June 2018) - Kanjilal, Tiyasha; Panda, Jigisha; Datta, Siddhartha
Highlights: Batch scale aerobic removal of toxic carbendazim fungicide and COD from agrochemical effluent. Bioremediation efficiency of 87.2% for 100 mg L −1 of the fungicide CBZ using single potential bacterial strain Brevibacillus sp. C17 (T4). One of the very few studies deducing substrate utilization rate (Us ) of the biodegradation process. DKR adsorption isotherm model predicts the mechanism of CBZ removal using strain Brevibacillus sp. C17. Phyto-toxicity analysis of real effluent and CBZ aqueous solution after bacterial treatment. Abstract: An indigenous bacterium Brevibacillus panacihumi C17 was isolated from agrochemical waste effluent (Kolkata area, India). The isolate showed an efficient degradation capacity of a toxic fungicide Carbendazim (CBZ) (300 mg L −1 ), frequently used in agricultural field in that area. The present research is one of the very few growth dynamics studies showing the substrate utilization rate (Us = 0.91) of the bacterium, also the specific growth rate which was observed to be 0.173 h −1 . Degradation studies revealed the maximum degradation (87.25%) was obtained at 100 mg L −1 at incubation time of 36 h, pH 7.0 and speed of 180 rpm beyond this the degradation was found to decline. The kinetic growth parameter modeling indicated that the process showed best fitting of the experimental data in Logistic function (R 2 = 0.94) as compared to others. Analytical studies of SEM, FTIR and XRD revealed the CBZ degradation mechanism by bio-sorption process occurring on the outer cell surface using adsorption energy. It was observed that the bio-sorption process followed the DKR isotherm model (R 2 = 0.921). Strain Brevibacillus sp. C17 was observed to reduce chemical oxygen demand (COD) by 85± 2.5% of the agrochemical waste effluent (COD 880 mg L −1 ) within 50 h of batch treatment. One of the important observations is the toxicity analysis of the real effluent and aqueous solution of CBZ after the bacterial treatment which indicated the environmental friendly behavior of the bio-treatment.